Peran Sumber Ortet, Nomor Daun dan Waktu Inkubasi Terhadap Hasil Kalus Kelapa Sawit (Elaeis guineensis Jacq.) - Ernayunita Ernayunita; Erwin Nazri; Retno Diah Setiowati; Hernawan Yuli Rahmadi; Yenni Yenni (Jurnal Penelitian Kelapa Sawit, 2022)
Callus production is an important key stage to reproduce oil palm through tissue culture in determining the number of produced clones. Callus production rate were affected by culture medium, organ, ortet genotypes and incubation time in the culture room. Leaf of four different individuals from two genotype: DS29D x LM2T dan BJ126D x LM2T were used as ortet on this study and only leaf number -4, -5, -6, -7 and -8 were used as an explant. Callus production of each ortet source was observed monthly and used as a parameter to determine the performance of each ortet. The result showed that BJ126D x LM2T as an ortet source had significantly higher callus production compared to DS29D x LM2T. Meanwhile the callus production from different leaf number were not significantly different. The first 6 months of explant incubation was the best time to produce callus